Verification of suitable height data acquisition method for three-dimensional national digital cadastral database - Abdul Rahim, Ajibah (2014)
This thesis presents a study on methods of height data acquisition towards the implementation of three-dimensional coordinates for three-dimensional National Digital Cadastral Database. At present, Malaysia’s cadastre system uses a two-dimensional system. This current system stores information in two-dimensional coordinates planimetric. The existing system is barely providing more realistic and meaningful information to users. The Department of Survey and Mapping Malaysia is trying to develop a hybrid cadastre model by adding three-dimensional coordinates into land parcels. Somehow, there are some matters must take into consideration. One of the matters is the method of data collection. This study is an attempt to verify some possible techniques for data collection of X, Y, and Z coordinates. In this research, the height data is extracted from three different sources which are data from Light Detection and Ranging positioning, Global Positioning System, and topographic digital map. Then, a comparison between those techniques is made by considering the difference in accuracy of height values and other aspects related. The final output is the suitable method for data acquisition in which all three methods are best for implementation by depending on the availability of data at specific area and the usage of them for certain applications. The method selected in the final result is practical to be applied based on Malaysian cadastral environment